Association between childhood asthma and chronic obstructive pulmonary disease in later life - Hirayama, F.; Lee, Andy (SAGE Publications Inc., 2015)
Persistent chronic inflammation and impaired lung growth due to asthma in childhood may have long-term impact on pulmonary function and increase susceptibility to chronic obstructive pulmonary disease (COPD) in later life. To investigate whether childhood asthma is associated with adult lung function and the risk of developing COPD among Japanese older adults, a case-control study was conducted in central Japan. A total of 300 patients with COPD aged 50 to 75 years were referred by respiratory physicians, while 400 controls were recruited from the community. All participants underwent spirometric measurements of lung function. Information on childhood asthma, demographic characteristics, and lifestyle characteristics was obtained by face-to-face interview using a structured questionnaire. The prevalence of childhood asthma was higher (P =.015) among the cases (6.3%) than among the control group (2.4%). Childhood asthma was significantly associated with the risk of COPD (adjusted odds ratio 3.32, 95% confidence interval 1.05-10.45). Participants with childhood asthma had lower (P =.010) forced expiratory volume in 1 second (mean 1.63 L, standard deviation [SD] 0.64 L) than those without (mean 2.04 L, SD 0.75 L). However, the adjusted lung function difference did not attain statistical significance after controlling for confounding variables such as age and cumulative smoking exposure. The epidemiological evidence suggested a positive association between childhood asthma and COPD in later life. Further study of the effect of adequate childhood asthma treatment on future risk of COPD should be undertaken.